Tobacco smoking prevalence in pregnant women: metanalysis of cross sectional studies. (30th September 2020) - Restivo, V; Pizzo, S; Marrella, A; Caracci, F; Vitale, F; Casuccio, A
Abstract: Background: Notwithstanding tobacco smoking during pregnancy is associated with negative health outcomes, its prevalence was not included by worldwide surveillance system. The main objective was to estimate the number of women who had smoked at least one cigarette during her pregnancy in comparison to not smoking women. Methods: A systematic review and metanalysis was conducted searching on MEDLINE, Pubmed and Scopus on the 2 January 2020. Keywords were searched with English language limits from 2017 to 2019. Three authors independently screened all titles and abstracts applying the inclusion criteria, extracted the data, filled a database and two other authors assessed doubt eligibility. Quality was assessed by the NOS scale and the prevalence of smoking during pregnancy was assessed dividing the number of women smoking by the total number of pregnant women reported in the studies. Results: A total of 1424 articles were screened and 726 were evaluated to be included in the final database of 234 articles. Of these, 85 were properly designed as cross-sectional, 85 were conducted as secondary analysis of cohort, and 64 were population-based studies. The overall smoking prevalence during pregnancy was 12% (95% CI 11%-13%) with an increase to 14% (95%CI 12%-15%) for studies that had smoking as the primary endpoint. In the metaregression analysis, the risk of smoking increased in South America (meta regression coefficent [MC]=0.46, p = 0.02). On the other hand, smoking prevalence decreased during time (studies conducted from 2000 to 2010 MC=-0.15, p = 0.008 and studies conducted after 2010 MC=-0.11, p = 0.04). Conclusions: This study revealed a high prevalence of smoking during pregnancy worldwide with higher values than reported in another metanalysis conducted from 1985 to 2016. However, prevalence decreased during the three years considered and was higher in some countries that need more preventive interventions. Key messages: Women of childbearing age need to be educated about the potential detrimental effects of tobacco use on the developing fetus and infant. Evidence-based smoking cessation interventions should be integrated into routine prenatal care.